STUDENTS’ PERCEPTION OF TEACHERS’ STRATEGY IN TEACHING ENGLISH - Ahmad Ahmad; Suziyanti Suziyanti (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
The purpose of this research is to know students' perception of teachers' strategy in teaching English of MTs Nurul Huda Parit 5 Sungai Luar. This research design is descriptive quantitative. The total populations are 195 students that consist of 98 males and 97 females. So, the sampling process was a total sampling because all students were chosen as the samples. To collect the data, the researcher used the questionnaire as the research instruments. From the data analysis, it was known that students’ perception on teachers’ strategy in teaching English at the fifth generation in 2015 of MTs Nurul Huda Parit 5 Sungai Luar in this research is categorized as good where the percentage is 86.42%. This percentage counted as good perception so the researcher can conclude that students' perception of teachers' strategy in teaching English as a good perception.